A New Computational Method for Protein–Ligand Binding Thermodynamics. (5th February 2019) - Chong, Song‐Ho; Ham, Sihyun
Abstract : We develop a new computational method for protein–ligand binding thermodynamics that combines alchemical transformations and the liquid theory. This method requires only the solute configurations during alchemical transformations, and solvent effects are incorporated through the solvation free energy. It is demonstrated that the new method yields the relative binding free energy that agrees well with the one from the conventional explicit solvent‐free energy simulations. The development reported here opens up new possibilities for faster binding free energy computations and easier access to the enthalpy and entropy components. Abstract :